Dynamics of coral rubble on reef flats: from individual clast mobilisation to rubble strip morphological change - Aitana Gea-Neuhaus; Tim Scott; Gerd Masselink; Ana Vila-Concejo; Paul S. Kench; Mathilde Lindhart; Floortje E. Roelvink; Tom Hamilton; Ke Lin; Xianfeng Wang (Marine Geology, 2026)

Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Mapping biological and chemical dimensions of antimicrobial resistance pollution and exposures due to treated wastewater discharges into US surface waters at the national scale - N.N. Khan; J. Jiang; M. Islam; H. Quon; R.L. Muenich; N. Rudko; S. Kamanmalek; J. Rice-Boayue; E. Garner; P. Westerhoff; A. Pruden; K.A. Hamilton (Environmental Pollution, 2026)

Is Wildfire Planning Evolving to Support Communities? Taking Stock of 20 years of Community Wildfire Protection Plans in the state of Colorado, United States - Jennifer Brousseau; Karissa Courtney; Maya Daurio; Matthew Hamilton; Antony S. Cheng; Cody Evers; A. Paige Fischer; Harrison Fried; Aidan Lyde; Emily Palsa; Max Nielsen-Pincus; Hallie Stelzle; et al. (Socio-Ecological Practice Research, 2026)

The uncontrolled rise of performance peptides: reasons for concern and a call for scientific and regulatory action - Marcel S. B. Arruda; Monique C. Gonçalves; Marcus V. S. Campos; Rafael A. Azevedo; Andresa R. Casale; Jorge Hallak; Hamilton Roschel; Bruno Gualano (European Journal of Applied Physiology, 2026)

Scanning the horizon for harmful cyanobacterial blooms - Xuexiu Chang; Hugh J. MacIsaac; Ingrid Chorus; George S. Bullerjahn; Rainer Kurmayer; Chi-Yong Ahn; Xiangzhen Kong; Steven W. Wilhelm; Susanna A. Wood; Xiangming Tang; Hans W. Paerl; Sabine Hilt; et al. (Trends in Ecology & Evolution, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Adverse childhood experiences, adult adiposity, and risk of young-onset breast cancer subtypes in a population-based case-control study - Lydia Marcus Post; Young Ik Cho; James Topitzes; DPhuong Do; Dorothy R. Pathak; Ann S. Hamilton; Amani M. Nuru-Jeter; Kelly A. Hirko; Jamila L. Kwarteng; Richard Houang; Ann G. Schwartz; Ellen M. Velie (Cancer Causes & Control, 2026)
Purpose Adverse childhood experiences (ACEs) are hypothesized to increase breast cancer risk via social and physiological pathways, yet associations between ACEs and young-onset breast cancer (BC) subtypes–and potential mediators (e.g., adiposity) of these associations–are largely unstudied. We sought to evaluate associations between ACEs and young-onset BC molecular subtypes, and the potential mediating effects of adiposity, in a population-based case–control study of invasive young-onset BC. Methods Cases (n = 1,754) were identified from the Los Angeles County and Metropolitan Detroit SEER registries, 2010–2015, and area-based, frequency-matched controls (n = 1,350) sampled from the 2010 Census. Associations between ACEs aged < 18 years and young-onset BC (diagnosed ages 20 to < 50 years), overall and by subtype (luminal A, luminal B, HER2 + , triple negative [TN]), were examined using weighted logistic regression. Adult adiposity (i.e., body mass index 12 months before diagnosis, waist circumference at interview) was evaluated as a mediator of these associations using weighted path analyses. Results ACEs (≥ 1 vs 0) were not significantly associated with young-onset BC (all p trend > 0.10); however, reporting one ACE (vs 0) was associated with TN (odds ratio [OR] = 1.85 [95% confidence interval [95%CI] = 1.08–3.16]). For individual ACEs, death of a loved one (vs 0 ACEs) was associated with HER2 + (OR = 2.50 [95%CI = 1.06–5.88]) and potentially TN (OR = 1.72 [95%CI = 0.96–3.10]) young-onset BC; other associations were non-significant. In path analyses, ACEs had a significant total effect on luminal A (β = 0.08, p = 0.03) and TN (β = 0.13, p < 0.01) tumors, with adiposity mitigating this association for luminal A tumors (β = -0.01, p = 0.04; TN β = 0.00, p > 0.05). Conclusions Bereavement during childhood was associated with higher odds of HER2 + young-onset BC, and there was some evidence of an association between ACEs and other young-onset BC subtypes, particularly TN.

Petrogenesis and Provenance of Unique Amphibole-Bearing Carbonaceous Chondrite Almahata Sitta 202: Further Evidence for a Ceres-Sized, Water-Rich Parent Body - Cyrena A. Goodrich; Victoria E. Hamilton; Michael E. Zolensky; Noriko Kita; Issaku Kohl; Lauren Tafla; Robert J. Macke; Takahiro Hiroi; Yoko Kebukawa; Wayne Buckley; Jacob B. Setera; Justin I. Simon; et al. (Geochimica et Cosmochimica Acta, 2026)

Exploring trait- and state-based dietary restraint using ecological momentary assessment - Rebecca L. Elsworth; Elanor C. Hinton; Julian P. Hamilton-Shield; Natalia S. Lawrence; Jeffrey M. Brunstrom (Appetite, 2026)

Cleaning products and classes associated with poor respiratory health - Xin Dai; Michael J. Abramson; Garun S. Hamilton; Bruce R. Thompson; Cecilie Svanes; Geza Benke; Sonia Kaushik; Shyamali C. Dharmage; Caroline J. Lodge (Environmental Science and Pollution Research, 2026)
Exposure to cleaning products may harm the lungs, mainly through inhalation of irritants and sensitising chemicals, which can induce airway inflammation and bronchial hyperresponsiveness. Given increased use of multiple cleaning products at work and home, understanding the impacts of their interplay, rather than individual exposures, is critical but has not been investigated to date. We aim to investigate the cross-sectional association between exposure to cleaning products at home and/or in the workplace and respiratory health. We conducted a cross-sectional analysis of 318 adults from the Melbourne arm of the European Community Respiratory Health Survey (ECRHS) III. Cleaning product exposure was assessed through questionnaires, categorising participant exposure into seven product groups. Latent class analysis was used to identify exposure classes. Adjusted multivariable regression modelled associations between cleaning product classes and respiratory outcomes. We identified four classes of exposure to cleaning products: “minimal users”, “light users”, “moderate users”, “heavy users”. The most exposed “heavy user group” characterised people using many different cleaning products on a weekly basis (especially bleach, sprays, polish, solvents, acids). This class was associated with increased risks of current asthma (OR, 3.24; 95% CI 1.19–8.77), and lower post-bronchodilator FEV 1 (z-score, −0.47) and FVC (−0.46) compared with “minimal users”. This work used a data-driven latent class approach to capture real-world cleaning product use patterns and relate them to respiratory health. We found that frequent use of multiple cleaning products was linked to more asthma and lower lung function, suggesting potential combined effects. These findings highlight the need for cleaning product standards and asthma care guidelines to mitigate risks associated with cleaning products.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Geomorphological features of Queen Charlotte Strait, Pacific coast of Canada, and their implications for ice-sheet retreat and relative sea-level changes during the last deglaciation - Zhen Li; Cooper D. Stacey; Tark S. Hamilton; Robert Kung; J. Vaughn Barrie; Jordan Eamer; John Shaw; Randolph J. Enkin (Quaternary International, 2026)

Ocean circulation, sea ice, and productivity simulated in Jones Sound, Canadian Arctic Archipelago, between 2003–2016 - Tyler Pelle; Paul G. Myers; Andrew Hamilton; Matthew Mazloff; Krista M. Soderlund; Lucas Beem; Donald D. Blankenship; Cyril Grima; Feras Habbal; Mark Skidmore; Jamin S. Greenbaum (Ocean Science, 2026)
Jones Sound is one of three critical waterways in the Canadian Arctic Archipelago that regulate liquid exchange between the Arctic Ocean and northern Atlantic Ocean. However, to date, no high-resolution ocean circulation model exists to study the recent evolution of Jones Sound, meaning that our understanding of circulation within the sound is based either on temporally and spatially sparse oceanographic observations or on extrapolating conditions within Baffin Bay, which has a more dense observational record. To address this, we develop a high-resolution (1/120°, 0.9 km) Jones Sound configuration of the Massachusetts Institute of Technology general circulation model and perform coupled ocean–sea ice–biological productivity simulations between 2003–2016. We find that circulation through Lady Ann Strait, Fram Sound, and Glacier Strait comprises 71 %, 14 %, and 15 % of the volumetric transport into and out of Jones Sound, with tidal flushing enhancing the magnitude of volumetric transport through Fram Sound. Warming Atlantic Water within western Baffin Bay flows into Jones Sound through Lady Ann Strait, becomes well-mixed, and circulates counterclockwise, encroaching on the terminus of most tidewater glaciers that line the eastern periphery of the sound. Furthermore, we find that sustained atmospheric and oceanic warming drives an 11 % reduction in the 2003–2016 mean summertime sea ice area, decreased wintertime sea ice thickness, and delayed onset of sea ice refreeze in the fall (thus lengthening the amount of time during which Jones Sound is ice-free). Tidal flushing through Cardigan Strait is critical in triggering melt-back of sea ice across northern Jones Sound. Lastly, this decline in sea ice increases light availability and, when coupled with warming of the subsurface waters in Jones Sound, facilitates enhanced primary productivity down to ∼ 21 m depth. While we note that the modeled warming signal in Baffin Bay is overestimated relative to observations, the results presented here improve our general understanding of how this critical waterway might change under continued polar-amplified global warming and underscores the need for sustained oceanographic observations in this region.

A reservoir-scale experiment to simulate recycled water inputs using artificial nutrient addition - M.A. Burford; S.J. Faggotter; S. Yu; D.P. Hamilton (Journal of Water Process Engineering, 2026)

Creating a global kelp forest conservation fundraising target: A 14-billion-dollar investment to “help the kelp” - Aaron M. Eger; Julia K. Baum; Tom Campbell; Bruno Cevallos Gil; Hannah S. Earp; Annalisa Falace; Jan Freiwald; Sara Hamilton; Steve I. Lonhart; Keith Rootsaert; Makena Åsa Rush; Jasmin Schuster; et al. (Biological Conservation, 2026)

Warming, cooling, and surface ice accumulation initiated by the release of water from the Athabasca Valles Flood Lava eruption on Mars - Saira S. Hamid; Laura Kerber; Matthew Varnam; Christopher W. Hamilton; Amanda B. Clarke (Earth and Planetary Science Letters, 2025)

Mapping Community Capacity to Reduce Vulnerability to Wildfire in Colorado, USA - Karissa Courtney; Federico Holm; Jennifer Brousseau; Sarah E. Walker; Antony S. Cheng; Matthew Hamilton; Max Nielsen-Pincus; Eric Toman; Jonathan Salerno (Forest Science, 2025)

Perturbation solution for second-harmonic generation in focused shear wave beams in soft solids - Philip G. Kaufinger; John M. Cormack; Kyle S. Spratt; Mark F. Hamilton (Wave Motion, 2025)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

Response to “Letter to the Editors” regarding “Ten-year exposure to household air pollution is associated with obstructive sleep apnoea” - Yaoyao Qian; Garun S. Hamilton; Chamara V. Senaratna; Jennifer L. Perret; Shyamali C. Dharmage (Environmental Research, 2025)

Ten-year exposure to household air pollution is associated with obstructive sleep apnoea - Yaoyao Qian; Garun S. Hamilton; Chamara V. Senaratna; Caroline J. Lodge; Michael J. Abramson; Xin Dai; Dinh S. Bui; Anurika P. De Silva; Paul S. Thomas; Bircan Erbas; Eugene H. Walters; Jennifer L. Perret; et al. (Environmental Research, 2025)

Unvegetated rivers no longer exist: Plant-landscape interactions in the Mojave and Amargosa rivers, SW USA - Hamilton A. Allport; Neil S. Davies (Geomorphology, 2025)

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Molecular modeling of a novel butane-substituted chalcone: from synthesis to comprehensive electron density analysis - Aécio V. B. Oliveira; Vitor S. Duarte; Renata Layse. G. de Paula; Jaqueline E. Queiroz; Gilberto L. B. de Aquino; Hamilton B. Napolitano; Ademir J. Camargo (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Molecular modeling of a chlorine chalcone with a potential platelet antiaggregant - Patricia R. S. Wenceslau; Vitor S. Duarte; Antônio S. N. Aguiar; Fernanda S. Fernandes; Guilherme R. Oliveira; Leonardo L. Borges; Hamilton B. Napolitano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

Wave-influenced connectivity and transport in submerged coral canopies - J. F. Hamilton; S. G. Monismith; J. R. Koseff (Coral Reefs, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Simultaneous quantification of carbaryl, chlorpyrifos, and paraquat in a municipal wastewater treatment plant by SPE-RP-HPLC–PDA-FD method - Kefa K. Onchoke; Joshua S. Hamilton; Anthony M. Broom; Gary Lopez (Environmental Monitoring and Assessment, 2025)

Exposure effects of synthetic glucocorticoid drugs on skeletal developmental and immune cell function in zebrafish - Charles M. Hamilton; Matthew J. Winter; Jonathan S. Ball; Maciej Trznadel; Luigi Margiotta-Casaluci; Stewart F. Owen; Charles R. Tyler (Science of The Total Environment, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Evaluating the influence of marine protected areas on surf zone fish - M. L. Marraffini; S. L. Hamilton; J. R. Marin Jarrin; M. Ladd; G. Koval; J. R. Madden; I. Mangino; L. M. Parker; K. A. Emery; K. Terhaar; D. M. Hubbard; R. J. Miller; et al. (Conservation Biology, 2024)
Marine protected areas (MPAs) globally serve conservation and fisheries management goals, generating positive effects in some marine ecosystems. Surf zones and sandy beaches, critical ecotones bridging land and sea, play a pivotal role in the life cycles of numerous fish species and serve as prime areas for subsistence and recreational fishing. Despite their significance, these areas remain understudied when evaluating the effects of MPAs. We compared surf zone fish assemblages inside and outside MPAs across 3 bioregions in California (USA). Using seines and baited remote underwater videos (BRUVs), we found differences in surf zone fish inside and outside MPAs in one region. Inside south region MPAs, we observed higher abundance (Tukey's honest significant difference [HSD] = 0.83, p = 0.0001) and richness (HSD = 0.22, p = 0.0001) in BRUVs and greater biomass (HSD = 0.32, p = 0.0002) in seine surveys compared with reference sites. Selected live‐bearing, fished taxa were positively affected by MPAs. Elasmobranchs displayed greater abundance in BRUV surveys and higher biomass in seine surveys inside south region MPAs (HSD = 0.35, p = 0.0003 and HSD = 0.23, p = 0.008, respectively). Although we observed no overall MPA signal for Embiotocidae, abundances of juvenile and large adult barred surfperch ( Amphistichus argenteus ), the most abundant fished species, were higher inside MPAs (K–S test D = 0.19, p

Examining ingested microplastics in fish: Considerations on filter pore size, analysis time, and material costs to design cost-effective projects - Caitlin Brawn; Bonnie M. Hamilton; Matthew S. Savoca; Mark L. Mallory; Jennifer F. Provencher (Marine Environmental Research, 2024)

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Developing a range-wide sampling framework for endangered species: a case study with light-footed Ridgway’s rail - Bryan S. Stevens; Courtney J. Conway; Kimberly A. Sawyer; Lauren Kershek; Giselle Block; Sandra Hamilton; Rebecca Kolstrom (Biodiversity and Conservation, 2024)
Monitoring provides the foundation for evaluating recovery of endangered species, yet many species lack monitoring programs designed to integrate a species’ unique attributes, specific monitoring objectives, and principles of statistical sampling theory. We developed a framework for monitoring and assessment of endangered light-footed Ridgway’s rails ( Rallus obsoletus levipes ) across their U.S. range, relative to multi-scale recovery goals. We created spatially explicit sample units and a sampling frame covering all potential habitat to facilitate range-wide probability sampling, and also built a model of the call-broadcast process commonly used to survey marsh birds that included heterogeneity in availability for detection and conditional detectability for each bird during each survey. We used the model to simulate 96 sampling strategies that included different levels of replication, multiple approaches for sample allocation amongst strata, and both simple random and weighted probability sampling (i.e., weights proportional to local rail abundance) of sample units within strata. Effective monitoring surveyed ≥ 20–30% of the sampling frame on ≥ 3 occasions, with weighted sample selection and more targeted sampling (50% of units) for strata that are key to species recovery. We also tested Bayesian N-mixture models for estimating abundance and show that multiple models provide reasonable estimates. This work lays the foundation for statistical sampling and multi-scale population estimation for an endangered bird, and for refinement of abundance estimation models. Moreover, this work provides a replicable process for building customized and statistically defensible sampling frameworks to assess recovery of endangered species that can be used for other sensitive species.

How water stability relates with timing, size, and community successions of harmful algal blooms: A case study in the Three Gorges Reservoir - Xuexing Yao; Zenghui Song; Guanglang Yang; Muhammad Waqas Yonas; Paul B. Hamilton; Amechi S. Nwankwegu; Oluwafemi Adeyeye; Wei Huang; Xiaojiao Luo; Abdelrahman M. Hassaan; G. Douglas Haffner; Lei Zhang (Marine Pollution Bulletin, 2024)

Simulating adaptive grazing management on soil organic carbon in the Southeast U.S.A. using MEMS 2 - Rafael S. Santos; Emma K. Hamilton; Paige L. Stanley; Keith Paustian; M. Francesca Cotrufo; Yao Zhang (Journal of Environmental Management, 2024)

Does salinity mediate the toxicity of perfluorooctanesulfonic acid (PFOS) in an estuarine fish? - Lucy E. Burcham; Tyler D. Hoskins; Elizabeth B. Allmon; Meredith N. Scherer; Anna G. Bushong; Matthew T. Hamilton; Sini Macheri; Grace S. Coogan; Youn J. Choi; Linda S. Lee; Maria S. Sepúlveda (Marine Pollution Bulletin, 2024)

Wastewater-based epidemiology as a public health resource in low- and middle-income settings - K.A. Hamilton; M.J. Wade; K.G. Barnes; R.A. Street; S. Paterson (Environmental Pollution, 2024)

Sr/Ca ratios indicate frugivory versus folivory in primates: a case study using handheld XRF in Kibale National Park, Uganda - M. I. Hamilton; B. L. Drake; E. Dzhinenko; A. Galloway; S. V. Nelson (Oecologia, 2024)

Migration of transition metals and potential for carbon mineralization during acid leaching of processed kimberlite from Venetia diamond mine, South Africa - Baolin Wang; Nina Zeyen; Sasha Wilson; Makoto J. Honda-McNeil; Jessica L. Hamilton; Konstantin Von Gunten; Daniel S. Alessi; Thomas R. Jones; David J. Paterson; Gordon Southam (Applied Geochemistry, 2024)

Exploring vaginal discharge scoring to assess clinical metritis severity: Comparison between intrauterine dextrose and systemic antibiotics treatments - J. Hamilton; E. Jimenez; P. Zarei; J. Lection; R. Sorto; E. Hovingh; M. Martinez; S. Bas; A.A. Barragan (The Veterinary Journal, 2024)

Spatial and temporal factors influencing wildlife use of overpass crossing structures and landscape siphons along a major canal - Kaela M. Hamilton; Thomas Bommarito; Jesse S. Lewis (Biological Conservation, 2024)

Degradation of the 2014–2015 Holuhraun vent-proximal edifice in Iceland - S. S. Sutton; J. A. Richardson; P. L. Whelley; S. P. Scheidt; C. W. Hamilton (Bulletin of Volcanology, 2024)
The earliest stages of volcanic vent degradation are rarely measured, leaving a gap in the knowledge that informs landform degradation models of cinder cones and other monogenetic vent structures. We documented the initial degradation of a 500-m-long spatter rampart at the primary vent of the 2014–2015 Holuhraun eruption in northern Iceland with high-resolution topographic change maps derived from terrestrial laser scanning (TLS) and photogrammetric surveys using an unoccupied aircraft system (UAS). Topographic differencing shows a total negative volume change of 42,637 m 3 , and a total positive volume change (basal deposition) of 10,304 m 3 (primarily as deposition at the base of steeply sloping surfaces). Two distinct styles of volume changes were observed on the interior and exterior of the spatter rampart. Material on the interior of the vent was removed from oversteepened slopes by discrete rockfalls, while diffusive processes were qualitatively evident on the exterior slopes. We propose a novel conceptual landform evolution model for spatter ramparts that combines rockfall processes on the interior walls, diffusive gravitational sliding on the exterior slopes, and incorporates cooling contraction and compaction over the entire edifice to describe the observed modes of topographic change during the onset of degradation. Potential hazards at fresh spatter ramparts are rockfalls at high slope areas of the vent interior walls where contacts between spatter clasts are prone to weakening by fumarolic activity, weathering, and settling. To capture such hazards, our data suggest a cadence for monitoring changes yearly for the first few years post-eruption, and at longer intervals thereafter.

Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

Development of Momentary Appetite Capture (MAC): A versatile tool for monitoring appetite over long periods - Rebecca L. Elsworth; Elanor C. Hinton; Annika N. Flynn; Lucy H. Merrell; Julian P. Hamilton-Shield; Natalia S. Lawrence; Jeffrey M. Brunstrom (Appetite, 2024)

A microbial risk assessor's guide to Valley Fever (Coccidioides spp.): Case study and review of risk factors - David Kahn; William Chen; Yarrow Linden; Karalee A. Corbeil; Sarah Lowry; Ciara A. Higham; Karla S. Mendez; Paige Burch; Taylor DiFondi; Marc Verhougstraete; Anneclaire J. De Roos; Charles N. Haas; et al. (Science of The Total Environment, 2024)

Synthesis, characterization, and supramolecular analysis of a novel chalcone derivative: exploring nonlinear optical applications - Luiz B. Costa; Cristiane A. F. E. Santos; Jaqueline E. Queiroz; Antônio S. N. Aguiar; Lóide O. Sallum; Jean M. F. Custodio; Gilberto L. B. Aquino; Ademir J. Camargo; Clodoaldo Valverde; Hamilton B. Napolitano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Structural-based analysis of sulfonamide derivatives: from solid states to acetolactate synthase enzyme interactions - Antônio S. N. Aguiar; Rogério F. Costa; Leonardo L. Borges; Lucas D. Dias; Hamilton B. Napolitano (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Treatment with PB125® Increases Femoral Long Bone Strength in 15-Month-Old Female Hartley Guinea Pigs - K. M. Andrie; D. R. Palmer; O. Wahl; S. Bork; M. Campbell; M. A. Walsh; J. Sanford; R. V. Musci; Karyn L. Hamilton; Kelly S. Santangelo; Christian M. Puttlitz (Annals of Biomedical Engineering, 2024)

Lifetime alcohol consumption patterns and young-onset breast cancer by subtype among Non-Hispanic Black and White women in the Young Women’s Health History Study - Kelly A. Hirko; Darek R. Lucas; Dorothy R. Pathak; Ann S. Hamilton; Lydia M. Post; Ugonna Ihenacho; Nicole Bohme Carnegie; Richard T. Houang; Kendra Schwartz; Ellen M. Velie (Cancer Causes & Control, 2024)

Field-testing solutions for drinking water quality monitoring in low- and middle-income regions and case studies from Latin American, African and Asian countries - N. Pichel; F. Hymnô de Souza; L.P. Sabogal-Paz; P.K. Shah; N. Adhikari; S. Pandey; B.M. Shrestha; S. Gaihre; D.A. Pineda-Marulanda; M. Hincapie; K. Luwe; S. Kumwenda; et al. (Journal of Environmental Chemical Engineering, 2023)

Predictive geochemical mapping using machine learning in western Kenya - Olivier S. Humphrey; Mark Cave; Elliott M. Hamilton; Odipo Osano; Diana Menya; Michael J. Watts (Geoderma Regional, 2023)

Suspected anthropogenic microparticle ingestion by Icelandic capelin - Caitlin Brawn; Bonnie M. Hamilton; Matthew S. Savoca; Birkir Bardarson; Jesse C. Vermaire; Jennifer Provencher (Marine Pollution Bulletin, 2023)

Blue carbon pathways for climate mitigation: Known, emerging and unlikely - Jennifer Howard; Ariana E. Sutton-Grier; Lindsey S. Smart; Christian C. Lopes; Jill Hamilton; Joan Kleypas; Stefanie Simpson; Jennifer McGowan; Albert Pessarrodona; Heidi K. Alleway; Emily Landis (Marine Policy, 2023)

From green to orange: The change in biochemical composition of phototrophic-mixotrophic Chromochloris zofingiensis in pilot-scale photobioreactors - Eleanor E. Wood; Michael E. Ross; Sébastien Jubeau; Valéria Montalescot; Karen MacKechnie; Ryan E. Marchington; Matthew P. Davey; Sharon McNeill; Callum Hamilton; Michele S. Stanley (Algal Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

ACMT Position Statement: End the Use of the Term “Excited Delirium” - Andrew I. Stolbach; Paul I. Dargan; Howard A. Greller; Richard J. Hamilton; Kelly Johnson-Arbor; Brian Patrick Murray; Daniel Ovakim; Laura Tormoehlen; Lewis S. Nelson; Sukhshant Atti; Jeffrey N. Bernstein; Caitlin Bonney; et al. (Journal of Medical Toxicology, 2023)

Kinetics, mechanism, and tautomerism in ametryn acid hydrolysis: From molecular structure to environmental impacts - Bruno Ramos; Wesley F. Vaz; Luan F. Diniz; Flavio O. Sanches Neto; Julio C.O. Ribeiro; Valter H. Carvalho-Silva; Antonio Carlos S.C. Teixeira; Caue Ribeiro; Hamilton B. Napolitano; Paulo S. Carvalho (Chemosphere, 2023)

Tritium across the hydrologic systems of southern Ontario, Canada: implications for groundwater age dating in the Great Lakes Basin - E. H. Priebe; S. M. Hamilton; A. Lemieux; D. J. Rowan; I. D. Clark (Hydrogeology Journal, 2023)

Abiotic reduction of nitrate to ammonium by iron (oxy)(hydr)oxides and its stable isotope (δ15N, δ18O) dynamics - Xin Wang; Naomi S. Wells; Wei Xiao; Jessica L. Hamilton; Adele M. Jones; Richard N. Collins (Geochimica et Cosmochimica Acta, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Electrochemically assisted photocatalytic degradation of contaminants of emerging concern in simulated wastewater using WO3 – Elucidation of mechanisms - A. Tolosana-Moranchel; S. McMichael; J.W.J. Hamilton; J.A. Byrne; P. Fernández-Ibañez (Chemical Engineering Journal, 2023)

Ranking the risk of CO2 emissions from seagrass soil carbon stocks under global change threats - Martin Dahl; Kathryn McMahon; Paul S. Lavery; Serena H. Hamilton; Catherine E. Lovelock; Oscar Serrano (Global Environmental Change, 2023)

Affecting behavioural change through empowerment: conceptual insights from theory and agricultural case studies in South Asia - Serena H. Hamilton; Wendy S. Merritt; Lucy Carter; Arnab Chakraborty; Michaela Cosijn; Lilly Lim-Camacho; Rajeshwar Mishra; Geoff Syme; Mahanambrota Das; Dhananjay Ray (Regional Environmental Change, 2022)
Affecting behavioural change is a common underlying goal across environmental and agricultural sciences, from climate change mitigation and adaptation, biodiversity conservation, water management, to crop diversification. However, many projects fail to drive or sustain change despite sound science and good intentions. This paper draws on existing theories of behavioural change to construct a conceptual framework that explores pathways to initiate and sustain change through the lens of empowerment, self-efficacy and agency. The framework is demonstrated with case studies from a project in India and Bangladesh that examined social inclusion of marginalised and poor farmers in the context of intensifying agriculture. The framework and case studies highlight that a number of conditions are needed to affect meaningful change including that target beneficiaries are suitably motivated, believe in their own capability and power to enact change and have access to the necessary resources. We propose the framework as a tool to help project teams explore the underlying elements of the process of change when designing, implementing and assessing agricultural or environmental projects and interventions. We contend that behavioural and social change needs to be explicitly fostered in such endeavours to achieve better and longer-term outcomes for the people and environment.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The relevance of pedigrees in the conservation genomics era - Stephanie J. Galla; Liz Brown; Yvette Couch‐Lewis (Ngāi Tahu: Te Hapū o Ngāti Wheke, Ngāti Waewae); Ilina Cubrinovska; Daryl Eason; Rebecca M. Gooley; Jill A. Hamilton; Julie A. Heath; Samantha S. Hauser; Emily K. Latch; Marjorie D. Matocq; Anne Richardson; et al. (Molecular Ecology, 2022)
Over the past 50 years conservation genetics has developed a substantive toolbox to inform species management. One of the most long‐standing tools available to manage genetics—the pedigree—has been widely used to characterize diversity and maximize evolutionary potential in threatened populations. Now, with the ability to use high throughput sequencing to estimate relatedness, inbreeding, and genome‐wide functional diversity, some have asked whether it is warranted for conservation biologists to continue collecting and collating pedigrees for species management. In this perspective, we argue that pedigrees remain a relevant tool, and when combined with genomic data, create an invaluable resource for conservation genomic management. Genomic data can address pedigree pitfalls (e.g., founder relatedness, missing data, uncertainty), and in return robust pedigrees allow for more nuanced research design, including well‐informed sampling strategies and quantitative analyses (e.g., heritability, linkage) to better inform genomic inquiry. We further contend that building and maintaining pedigrees provides an opportunity to strengthen trusted relationships among conservation researchers, practitioners, Indigenous Peoples, and Local Communities.

Prevalence and predictors of REM sleep without atonia in a sleep clinic population - C. Yu; J. Stonehouse; A. R. Turton; S. A. Joosten; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Theory, methods, and operational results of the Young Women’s Health History Study: a study of young-onset breast cancer incidence in Black and White women - Ellen M. Velie; Lydia R. Marcus; Dorothy R. Pathak; Ann S. Hamilton; Ralph DiGaetano; Ron Klinger; Bibi Gollapudi; Richard Houang; Nicole Carnegie; L. Karl Olson; Amani Allen; Zhenzhen Zhang; et al. (Cancer Causes & Control, 2021)
Purpose The etiology of young-onset breast cancer (BC) is poorly understood, despite its greater likelihood of being hormone receptor-negative with a worse prognosis and persistent racial and socioeconomic inequities. We conducted a population-based case–control study of BC among young Black and White women and here discuss the theory that informed our study, exposures collected, study methods, and operational results. Methods Cases were non-Hispanic Black (NHB) and White (NHW) women age 20–49 years with invasive BC in metropolitan Detroit and Los Angeles County SEER registries 2010–2015. Controls were identified through area-based sampling from the U.S. census and frequency matched to cases on study site, race, and age. An eco-social theory of health informed life-course exposures collected from in-person interviews, including socioeconomic, reproductive, and energy balance factors. Measured anthropometry, blood (or saliva), and among cases SEER tumor characteristics and tumor tissue (from a subset of cases) were also collected. Results Of 5,309 identified potentially eligible cases, 2,720 sampled participants were screened and 1,812 completed interviews (682 NHB, 1140 NHW; response rate (RR): 60%). Of 24,612 sampled control households 18,612 were rostered, 2,716 participants were sampled and screened, and 1,381 completed interviews (665 NHB, 716 NHW; RR: 53%). Ninety-nine% of participants completed the main interview, 82% provided blood or saliva (75% blood only), and SEER tumor characteristics (including ER, PR and HER2 status) were obtained from 96% of cases. Conclusions Results from the successfully established YWHHS should expand our understanding of young-onset BC etiology overall and by tumor type and identify sources of racial and socioeconomic inequities in BC.

Assessing prevalence and correlates of blue-colored flesh in lingcod (Ophiodon elongatus) across their geographic range - Aaron W. E. Galloway; Anne H. Beaudreau; Michael D. Thomas; Bonnie L. Basnett; Laurel S. Lam; Scott L. Hamilton; Kelly S. Andrews; Julie B. Schram; Jessica Watson; Jameal F. Samhouri (Marine Biology, 2021)
Intraspecific variation in external and internal pigmentation is common among fishes and explained by a variety of biological and ecological factors. Blue-colored flesh in fishes is relatively rare but has been documented in some species of the sculpin, greenling, and perch families. Diet, starvation, photoprotection, and camouflage have all been suggested as proximate mechanisms driving blue flesh, but causal factors are poorly understood. We evaluated the relative importance of biological and spatial factors that could explain variation in blue coloration in 2021 lingcod ( Ophiodon elongatus ) captured across their range in the northeastern Pacific, from southeast Alaska to southern California. The probability of having blue flesh was highest for fish that were female, caught in shallower water, and smaller in body size. The incidence of blueness varied by region (4–25% of all fish) but was also confounded by differences in sex ratios of fish caught among regions. We analyzed the multivariate fatty acid composition of a subset of 175 fish from across the sampling range to test for differences in trophic biomarkers in blue lingcod. Lingcod fatty acid composition differed between regions and flesh colors but not between sexes. Blue-fleshed fish had lower concentrations of total fatty acids, 18:1ω-9, 16:1ω-7, 18:1ω-7, and ω-6 fatty acids, suggesting differences in energetics and energy storage in blue fish. While our data indicate potential links between diet and blue flesh in lingcod, important questions remain about the physiological mechanisms governing blueness and its biological consequences.

High contribution of methane in greenhouse gas emissions from a eutrophic lake: a mass balance synthesis - Arianto B. Santoso; David P. Hamilton; Louis A. Schipper; Ilia S. Ostrovsky; Chris H. Hendy (New Zealand Journal of Marine and Freshwater Research, 2021)
Lakes are ‘hotspots’ for greenhouse gas (GHG) emissions, primarily carbon dioxide (CO 2 ) and methane (CH 4 ). Understanding the processes regulating GHG emissions from lakes, and their temporal variability, is essential for more accurately quantifying the role of lakes in global GHG cycles. In this study, we identified the processes that affect CO 2 and CH 4 concentrations in a small (0.3 km 2 ) eutrophic monomictic lake (Okaro, New Zealand). A mass balance model was used to calculate changes in CO 2 and CH 4 storage in the lake as a result of internal cycling and atmospheric fluxes. To support model computations, CO 2 and CH 4 concentrations profiles were measured monthly over a one‐year period, in addition to temperature, dissolved oxygen and chlorophyll a . Annually, Lake Okaro acted as a sink of CO 2 from the atmosphere (425.4 mmol CO 2 m −2 y −1 ) and a source of CH 4 (553.4 mmol CH 4 m −2 y −1 ) equating to a net GHG emission (diffusive fluxes of CO 2 and CH 4 combined) of 0.22 kg CO 2 ‐eq m −2 y −1 . Although it may be viewed as conservative and applies only to diffusive fluxes, our study indicates that eutrophic lakes with high rates of primary production may act as a net source of GHGs.

Coastal Ocean Observing and Modeling Systems in Brazil: Initiatives and Future Perspectives - Guilherme Franz; Carlos A. E. Garcia; Janini Pereira; Luiz Paulo de Freitas Assad; Marcelo Rollnic; Luis Hamilton P. Garbossa; Letícia Cotrim da Cunha; Carlos A. D. Lentini; Paulo Nobre; Alexander Turra; Janice R. Trotte-Duhá; Mauro Cirano; et al. (Frontiers in Marine Science, 2021)
Coastal ocean observing and modeling systems (coastal observatories), connected with regional and global ocean systems, improve the quality of information and forecasts for effective management of safe and sustainable maritime activities. The public availability of systematic and long-term information of the ocean is an engine for the Blue Economy, boosting economic growth, employment, and innovation. An overview of some Brazilian initiatives is presented in this paper, involving universities, private companies, federal and state agencies, covering institutions from south to north of Brazil. Although these initiatives focus mainly on ocean physics, integrated efforts can extend the scope to include biogeochemistry and marine biodiversity, helping to address interdisciplinary problems. Existing initiatives can be connected, and new ones fostered, to fill in the gaps of temporal and spatial coverage of ocean monitoring in the vast oceanic area under Brazilian jurisdiction (nationally referred to as the Blue Amazon, in reference to the similar richness of the Amazon Forest). The alignment among national and regional initiatives, as well as with international programs, can be promoted if coordinated by a national-level organization, maximizing the return of public investment and socioeconomic benefits. In light of international examples, possible future institutional arrangements are discussed, leveraging from existing national public policies and international cooperation that Brazil is taking part. The United Nations Decade of Ocean Science for Sustainable Development is a timely opportunity to encourage an institutional arrangement to support and articulate an integrated network of coastal observatories in Brazil.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

Motor unit action potential amplitude during low torque fatiguing contractions versus high torque non-fatiguing contractions: a multilevel analysis - Kylie K. Harmon; Adam S. Hamilton; Brent D. Johnson; Frank J. Bartek; Ryan M. Girts; Rob J. MacLennan; Debbie L. Hahs-Vaughn; Matt S. Stock (European Journal of Applied Physiology, 2021)

Dietary intake, eating behavior and physical activity in individuals with and without obstructive sleep apnea - Caroline J. Beatty; Shane A. Landry; Joy Lee; Simon A. Joosten; Anthony Turton; Denise M. O’Driscoll; Ai-Ming Wong; Luke Thomson; Bradley A. Edwards; Garun S. Hamilton (Sleep and Biological Rhythms, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

Semiautomatic morphometric analysis of skeletal muscle obtained by needle biopsy in older adults - Henry J. Bonilla; Maria L. Messi; Khalima A. Sadieva; Craig A. Hamilton; Aron S. Buchman; Osvaldo Delbono (GeroScience, 2020)

Estimating cancer treatment intensity from SEER cancer registry data: methods and implications for population-based registry studies of pediatric cancers - Jessica L. Tobin; Stefanie M. Thomas; David R. Freyer; Ann S. Hamilton; Joel E. Milam (Cancer Causes & Control, 2020)

Effects of hypoxia on the behavior and physiology of kelp forest fishes - Evan G. Mattiasen; Neosha S Kashef; David M. Stafford; Cheryl A. Logan; Susan M. Sogard; Eric P. Bjorkstedt; Scott L. Hamilton (Global Change Biology, 2020)
Forecasts from climate models and oceanographic observations indicate increasing deoxygenation in the global oceans and an elevated frequency and intensity of hypoxic events in the coastal zone, which have the potential to affect marine biodiversity and fisheries. Exposure to low dissolved oxygen (DO) conditions may have deleterious effects on early life stages in fishes. This study aims to identify thresholds to hypoxia while testing behavioral and physiological responses of two congeneric species of kelp forest fish to four DO levels, ranging from normoxic to hypoxic (8.7, 6.0, 4.1, and 2.2 mg O 2 /L). Behavioral tests identified changes in exploratory behavior and turning bias (lateralization), whereas physiological tests focused on determining changes in hypoxia tolerance (pCrit), ventilation rates, and metabolic rates, with impacts on the resulting capacity for aerobic activity. Our findings indicated that copper rockfish ( Sebastes caurinus ) and blue rockfish ( Sebastes mystinus ) express sensitivity to hypoxia; however, the strength of the response differed between species. Copper rockfish exhibited reduced absolute lateralization and increased escape time at the lowest DO levels, whereas behavioral metrics for blue rockfish did not vary with oxygen level. Both species exhibited decreases in aerobic scope (as a function of reduced maximum metabolic rate) and increases in ventilation rates to compensate for decreasing oxygen levels. Blue rockfish had a lower pCrit and stronger acclimation response compared to copper rockfish. The differences expressed by each species suggest that acclimatization to changing ocean conditions may vary, even among related species that recruit to the same kelp forest habitat, leading to winners and losers under future ocean conditions. Exposure to hypoxia can decrease individual physiological fitness through metabolic and aerobic depression and changes to anti‐predator behavior, with implications for the outcome of ecological interactions and the management of fish stocks in the face of climate change.

Iodine status in western Kenya: a community-based cross-sectional survey of urinary and drinking water iodine concentrations - Michael J. Watts; Daniel R. S. Middleton; Andrew Marriott; Olivier S. Humphrey; Elliott Hamilton; Valerie McCormack; Diana Menya; Jessica Farebrother; Odipo Osano (Environmental Geochemistry and Health, 2020)

Energy Metabolism and Mitochondrial Superoxide Anion Production in Pre-symptomatic Striatal Neurons Derived from Human-Induced Pluripotent Stem Cells Expressing Mutant Huntingtin - James Hamilton; Tatiana Brustovetsky; Akshayalakshmi Sridhar; Yanling Pan; Theodore R. Cummins; Jason S. Meyer; Nickolay Brustovetsky (Molecular Neurobiology, 2020)

Limitations of trait‐based approaches for stressor assessment: The case of freshwater invertebrates and climate drivers - Anna T. Hamilton; Ralf B. Schäfer; Matthew I. Pyne; Bruce Chessman; Karan Kakouei; Kate S. Boersma; Piet F. M. Verdonschot; Ralf C. M. Verdonschot; Meryl Mims; Kieran Khamis; Britta Bierwagen; Jen Stamp (Global Change Biology, 2020)
The appeal of trait‐based approaches for assessing environmental vulnerabilities arises from the potential insight they provide into the mechanisms underlying the changes in populations and community structure. Traits can provide ecologically based explanations for observed responses to environmental changes, along with predictive power gained by developing relationships between traits and environmental variables. Despite these potential benefits, questions remain regarding the utility and limitations of these approaches, which we explore focusing on the following questions: (a) How reliable are predictions of biotic responses to changing conditions based on single trait–environment relationships? (b) What factors constrain detection of single trait–environment relationships, and how can they be addressed? (c) Can we use information on meta‐community processes to reveal conditions when assumptions underlying trait‐based studies are not met? We address these questions by reviewing published literature on aquatic invertebrate communities from stream ecosystems. Our findings help to define factors that influence the successful application of trait‐based approaches in addressing the complex, multifaceted effects of changing climate conditions on hydrologic and thermal regimes in stream ecosystems. Key conclusions are that observed relationships between traits and environmental stressors are often inconsistent with predefined hypotheses derived from current trait‐based thinking, particularly related to single trait–environment relationships. Factors that can influence findings of trait‐based assessments include intercorrelations of among traits and among environmental variables, spatial scale, strength of biotic interactions, intensity of habitat disturbance, degree of abiotic stress, and methods of trait characterization. Several recommendations are made for practice and further study to address these concerns, including using phylogenetic relatedness to address intercorrelation. With proper consideration of these issues, trait‐based assessment of organismal vulnerability to environmental changes can become a useful tool to conserve threatened populations into the future.

Racial/ethnic differences in patient experiences with health care in association with earlier stage at breast cancer diagnosis: findings from the SEER-CAHPS data - Albert J. Farias; Carol Y. Ochoa; Gabriela Toledo; Soo-In Bang; Ann S. Hamilton; Xianglin L. Du (Cancer Causes & Control, 2020)

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

Foraging consistency of coral reef fishes across environmental gradients in the central Pacific - Brian J. Zgliczynski; Gareth J. Williams; Scott L. Hamilton; Elisabeth G. Cordner; Michael D. Fox; Yoan Eynaud; Robert H. Michener; Les S. Kaufman; Stuart A. Sandin (Oecologia, 2019)

Iodine uptake, storage and translocation mechanisms in spinach (Spinacia oleracea L.) - O. S. Humphrey; S. D. Young; E. H. Bailey; N. M. J. Crout; E. L. Ander; E. M. Hamilton; M. J. Watts (Environmental Geochemistry and Health, 2019)

Biofilm Formation by Avian Pathogenic Escherichia coli is Not Related to In Vivo Pathogenicity - Suelle V. Rodrigues; Vanessa Laviniki; Karen A. Borges; Thales Q. Furian; Hamilton L. S. Moraes; Vladimir P. Nascimento; Carlos T. P. Salle (Current Microbiology, 2019)

Heparin impairs angiogenic signaling and compensatory lung growth after left pneumonectomy - Duy T. Dao; Lorenzo Anez-Bustillos; Jared Ourieff; Amy Pan; Paul D. Mitchell; Hiroko Kishikawa; Gillian L. Fell; Meredith A. Baker; Randolph S. Watnick; Hong Chen; Thomas E. Hamilton; Michael S. Rogers; et al. (Angiogenesis, 2018)

From Gondwana to GAAR landia: Evolutionary history and biogeography of ogre‐faced spiders ( Deinopis ) - Lisa Chamberland; Anne McHugh; Sarah Kechejian; Greta J. Binford; Jason E. Bond; Jonathan Coddington; Gaynor Dolman; Chris A. Hamilton; Mark S. Harvey; Matjaž Kuntner; Ingi Agnarsson (Journal of Biogeography, 2018)
Aim We explore the evolutionary history of the ogre‐faced spiders ( Deinopis ) from their Early Cretaceous origins to present day. Specifically, we investigate how vicariance and dispersal have shaped distribution patterns of this lineage. Within the Caribbean, we test the role of GAAR landia, a hypothesized land bridge that connected South America to the Greater Antilles during the Eocene–Oligocene transition (~35–33 Ma), in the biogeography of Deinopis . Taxon Araneae: Deinopidae: Deinopis . Location Caribbean islands, with additional global exemplars. Methods Combining standard Sanger sequence data with an Anchored Hybrid Enrichment ( AHE ) phylogenomic dataset, we use Bayesian inference to estimate the phylogenetic relationships of Deinopis . “BioGeo BEARS ” is used to test the GAAR landia hypothesis, and to pinpoint major dispersal events in the biogeographic history of Deinopis . Results The phylogeny supports the nesting of a Caribbean clade within a continental grade. Model comparisons indicate GAAR landia as the best fitting model, and the biogeographic analyses reflect the geologic history within the Caribbean. Ancient and recent overwater dispersal events are also indicated within this lineage. There is also an ancient 113 Ma split into Old and New World clades. Main Conclusions The Deinopis phylogeny corresponds well with geography. This is reflected in the support for the GAAR landia land bridge hypothesis and the phylogenetic relationships within and among Caribbean islands mirroring nuances of Caribbean geologic history. Overwater dispersal also plays an important role in the biogeographic history of this lineage as implicated in the colonization of the volcanic and sedimentary Lesser Antilles and in a “reverse” colonization of North America. The spider family Deinopidae is an ancient lineage with origins dating back to Gondwana. While overwater dispersal has clearly played a role in the biogeography of the genus, the Deinopis phylogeny bears a strong signature of ancient geological events.

Using hospital medical record data to assess the accuracy of the SEER Los Angeles Cancer Surveillance Program for initial treatment of prostate cancer: a small pilot study - Ryan D. Kraus; Ann S. Hamilton; Mari Carlos; Leslie K. Ballas (Cancer Causes & Control, 2018)

Interaction of preservation methods and radiation sterilization in human skin processing, with particular insight on the impact of the final water content and collagen disruption. Part I: process validation, water activity and collagen changes in tissues cryopreserved or processed using 50, 85 or 98% glycerol solutions - M. R. Herson; K. Hamilton; J. White; D. Alexander; S. Poniatowski; A. J. O’Connor; J. A. Werkmeister (Cell and Tissue Banking, 2018)

Apoptosis and expression of apoptosis-related genes in mouse intestinal tissue after whole-body proton exposure - Ashley Purgason; Ye Zhang; Stanley R. Hamilton; Daila S. Gridley; Ayodotun Sodipe; Olufisayo Jejelowo; Govindarajan T. Ramesh; Maria Moreno-Villanueva; Honglu Wu (Molecular and Cellular Biochemistry, 2018)

Constructed treatment wetlands provide habitat for zooplankton communities in agricultural peat lake catchments - Rebecca S. Eivers; Ian C. Duggan; David P. Hamilton; John M. Quinn (Wetlands, 2018)

Staying in place during times of change in Arctic Alaska: the implications of attachment, alternatives, and buffering - Henry P. Huntington; Philip A. Loring; Glenna Gannon; Shari Fox Gearheard; S. Craig Gerlach; Lawrence C. Hamilton (Regional Environmental Change, 2018)

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Pancreas specific expression of oncogenes in a porcine model - Martin F. Berthelsen; Morten M. Callesen; Tanja S. Østergaard; Ying Liu; Rong Li; Henrik Callesen; Frederik Dagnæs-Hansen; Stephen Hamilton-Dutoit; Jannik E. Jakobsen; Martin K. Thomsen (Transgenic Research, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

A Qualitative Exploration of Latinos’ Perceptions About Skin Cancer: the Role of Gender and Linguistic Acculturation - Vivian M. Rodríguez; Elyse Shuk; Guedy Arniella; C. Javier González; Francesca Gany; Jada G. Hamilton; Geoffrey S. Gold; Jennifer L. Hay (Journal of Cancer Education, 2017)

Syrian hamster neuroplasticity mechanisms fail as temperature declines to 15 °C, but histaminergic neuromodulation persists - Jock S. Hamilton; Sat M. Chau; Kevin J. Malins; Giancarlo G. Ibanez; John M. Horowitz; Barbara A. Horwitz (Journal of Comparative Physiology B, 2017)

Aerosols in the Pre-industrial Atmosphere - Kenneth S. Carslaw; Hamish Gordon; Douglas S. Hamilton; Jill S. Johnson; Leighton A. Regayre; M. Yoshioka; Kirsty J. Pringle (Current Climate Change Reports, 2017)

Multiple lines of evidence determine robust nutrient load limits required to safeguard a threatened lake/lagoon system - M. Schallenberg; D. P. Hamilton; A. S. Hicks; H. A. Robertson; M. Scarsbrook; B. Robertson; K. Wilson; D. Whaanga; H. F. E. Jones; K. Hamill (New Zealand Journal of Marine and Freshwater Research, 2017)
Three independent scientific lines of evidence were sought to determine the nutrient load limits to safeguard the macrophyte community of an intermittently closed and open lake/lagoon (ICOLL): (1) a literature review identified nitrogen load thresholds related to the collapse of macrophytes in similar systems in Australia, Europe and elsewhere, (2) an ICOLL expert carried out an assessment based on current local data and on data from 57 Australian coastal lakes and lagoons, and (3) a deterministic coupled hydrodynamic‐ecological model was developed and applied to simulate the ecological outcomes of several nutrient loading scenarios. The three lines of evidence converged on well‐defined nitrogen load estimates required to avoid the collapse of the macrophyte community. Uncertainties were slightly greater in relation to required phosphorus load limits, but the evidence still helped set a precautionary phosphorus load limit that accounted for these uncertainties. Thus, despite the challenges in setting load limits for complex ecosystems, multiple lines of evidence helped derive robust nutrient load limits for managing the ICOLL to safeguard values associated with a healthy macrophyte community.

Tissue recovery practices and bioburden: a systematic review - S. Brubaker; K. Lotherington; Jie Zhao; B. Hamilton; G. Rockl; A. Duong; A. Garibaldi; N. Simunovic; D. Alsop; D. Dao; R. Bessemer; O. R. Ayeni (Cell and Tissue Banking, 2016)

Chronic Ingestion of Coal Fly-Ash Contaminated Prey and Its Effects on Health and Immune Parameters in Juvenile American Alligators (Alligator mississippiensis) - John W. Finger; Matthew T. Hamilton; Brian S. Metts; Travis C. Glenn; Tracey D. Tuberville (Archives of Environmental Contamination and Toxicology, 2016)

Guiding principles for the development and application of solid-phase phosphorus adsorbents for freshwater ecosystems - G. B. Douglas; D. P. Hamilton; M. S. Robb; G. Pan; B. M. Spears; M. Lurling (Aquatic Ecology, 2016)

Investigating Cross‐Sectoral Synergies through Integrated Aquaculture, Fisheries, and Agriculture Phosphorus Assessments: A Case Study of Norway - Helen A. Hamilton; Eva Brod; Ola S. Hanserud; Erik O. Gracey; Magnus I. Vestrum; Anne Bøen; Franciska S. Steinhoff; Daniel B. Müller; Helge Brattebø (Journal of Industrial Ecology, 2016)
Summary Future phosphorus (P) scarcity and eutrophication risks demonstrate the need for systems‐wide P assessments. Despite the projected drastic increase in world‐wide fish production, P studies have yet to include the aquaculture and fisheries sectors, thus eliminating the possibility of assessing their relative importance and identifying opportunities for recycling. Using Norway as a case, this study presents the results of a current‐status integrated fisheries, aquaculture, and agriculture P flow analysis and identifies current sectoral linkages as well as potential cross‐sectoral synergies where P use can be optimized. A scenario was developed to shed light on how the projected 2050 fivefold Norwegian aquaculture growth will likely affect P demand and secondary P resources. The results indicate that, contrary to most other countries where agriculture dominates, in Norway, aquaculture and agriculture drive P consumption and losses at similar levels and secondary P recycling, both intra‐ and cross‐sectorally, is far from optimized. The scenario results suggest that the projected aquaculture growth will make the Norwegian aquaculture sector approximately 4 times as P intensive as compared to agriculture, in terms of both imported P and losses. This will create not only future environmental challenges, but also opportunities for cross‐sectoral P recycling that could help alleviate the mineral P demands of agriculture. Near‐term policy measures should focus on utilizing domestic fish scrap for animal husbandry and/or fish feed production. Long‐term efforts should focus on improving technology and environmental systems analysis methods to enable P recovery from aquaculture production and manure distribution in animal husbandry.

Modulation of microcystin congener abundance following nitrogen depletion of a Microcystis batch culture - Jonathan Puddick; Michèle R. Prinsep; Susanna A. Wood; S. Craig Cary; David P. Hamilton (Aquatic Ecology, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins - Przemyslaw Szafranski; Tomasz Gambin; Avinash V. Dharmadhikari; Kadir Caner Akdemir; Shalini N. Jhangiani; Jennifer Schuette; Nihal Godiwala; Svetlana A. Yatsenko; Jessica Sebastian; Suneeta Madan-Khetarpal; Urvashi Surti; Rosanna G. Abellar; et al. (Human Genetics, 2016)

The influence of status and the social environment on energy stores in a social fish - J. K. Hellmann; I. Y. Ligocki; C. M. O'Connor; A. R. Reddon; T. M. Farmer; S. E. Marsh‐Rollo; S. Balshine; I. M. Hamilton (Journal of Fish Biology, 2016)
This study explores how muscle and liver energy stores are linked with social status and the social environment in Neolamprologus pulcher , a cooperatively breeding fish that lives in colonies comprised of up to 200 distinct social groups. Subordinate muscle energy stores were positively correlated with the number of neighbouring social groups in the colony, but this pattern was not observed in dominant N. pulcher . Furthermore, liver energy stores were smaller in dominants living at the edge of the colony compared with those living in the colony centre, with no differences among subordinates in liver energy stores. Subordinate N. pulcher may build up large energy stores in the muscles to fuel rapid growth after dispersal, which could occur more frequently in high‐density environments. Dominant N. pulcher may use the more easily mobilized energy stores in the liver to fuel daily activities, which could be more energetically demanding on the edge of the colony as a result of the increased predation defence needed on the edge. Overall, this study demonstrates that both subordinate and dominant physiology in N. pulcher varies with characteristics of the social environment. Furthermore, dominant and subordinate energy storage strategies appear to differ due to status‐dependent variation in daily activities and variation in the need to prepare for future reproductive or dispersal opportunities.

The role of defensive ecological interactions in the evolution of conotoxins - J. R. Prashanth; S. Dutertre; A. H. Jin; V. Lavergne; B. Hamilton; F. C. Cardoso; J. Griffin; D. J. Venter; P. F. Alewood; R. J. Lewis (Molecular Ecology, 2016)
Venoms comprise of complex mixtures of peptides evolved for predation and defensive purposes. Remarkably, some carnivorous cone snails can inject two distinct venoms in response to predatory or defensive stimuli, providing a unique opportunity to study separately how different ecological pressures contribute to toxin diversification. Here, we report the extraordinary defensive strategy of the Rhizoconus subgenus of cone snails. The defensive venom from this worm‐hunting subgenus is unusually simple, almost exclusively composed of αD‐conotoxins instead of the ubiquitous αA‐conotoxins found in the more complex defensive venom of mollusc‐ and fish‐hunting cone snails. A similarly compartmentalized venom gland as those observed in the other dietary groups facilitates the deployment of this defensive venom. Transcriptomic analysis of a Conus vexillum venom gland revealed the αD‐conotoxins as the major transcripts, with lower amounts of 15 known and four new conotoxin superfamilies also detected with likely roles in prey capture. Our phylogenetic and molecular evolution analysis of the αD‐conotoxins from five subgenera of cone snails suggests they evolved episodically as part of a defensive strategy in the Rhizoconus subgenus. Thus, our results demonstrate an important role for defence in the evolution of conotoxins.

Western Juniper Management: Assessing Strategies for Improving Greater Sage-grouse Habitat and Rangeland Productivity - Shahla Farzan; Derek J. N. Young; Allison G. Dedrick; Matthew Hamilton; Erik C. Porse; Peter S. Coates; Gabriel Sampson (Environmental Management, 2015)

A rapid PCR-based test for identification of fifteen British bat species - P. B. Hamilton; T. M. Uren Webster; M. Basiewicz; E. V. Kennedy; E. S. R. De-Bastos; F. Mathews (Conservation Genetics Resources, 2015)

BAAD: a Biomass And Allometry Database for woody plants - Daniel S. Falster; Remko A. Duursma; Masae I. Ishihara; Diego R. Barneche; Richard G. FitzJohn; Angelica Vårhammar; Masahiro Aiba; Makoto Ando; Niels Anten; Michael J. Aspinwall; Jennifer L. Baltzer; Christopher Baraloto; et al. (Ecology, 2015)
Understanding how plants are constructed—i.e., how key size dimensions and the amount of mass invested in different tissues varies among individuals—is essential for modeling plant growth, carbon stocks, and energy fluxes in the terrestrial biosphere. Allocation patterns can differ through ontogeny, but also among coexisting species and among species adapted to different environments. While a variety of models dealing with biomass allocation exist, we lack a synthetic understanding of the underlying processes. This is partly due to the lack of suitable data sets for validating and parameterizing models. To that end, we present the Biomass And Allometry Database (BAAD) for woody plants. The BAAD contains 259 634 measurements collected in 176 different studies, from 21 084 individuals across 678 species. Most of these data come from existing publications. However, raw data were rarely made public at the time of publication. Thus, the BAAD contains data from different studies, transformed into standard units and variable names. The transformations were achieved using a common workflow for all raw data files. Other features that distinguish the BAAD are: (i) measurements were for individual plants rather than stand averages; (ii) individuals spanning a range of sizes were measured; (iii) plants from 0.01–100 m in height were included; and (iv) biomass was estimated directly, i.e., not indirectly via allometric equations (except in very large trees where biomass was estimated from detailed sub‐sampling). We included both wild and artificially grown plants. The data set contains the following size metrics: total leaf area; area of stem cross‐section including sapwood, heartwood, and bark; height of plant and crown base, crown area, and surface area; and the dry mass of leaf, stem, branches, sapwood, heartwood, bark, coarse roots, and fine root tissues. We also report other properties of individuals (age, leaf size, leaf mass per area, wood density, nitrogen content of leaves and wood), as well as information about the growing environment (location, light, experimental treatment, vegetation type) where available. It is our hope that making these data available will improve our ability to understand plant growth, ecosystem dynamics, and carbon cycling in the world's vegetation.

Cross‐sectional study to investigate the presence of salmon pancreas disease virus in wild and feral fish populations in 10 lakes, L os L agos R egion, C hile - R Alegría; G Arriagada; S Urcelay; C Hamilton‐West (Journal of Fish Diseases, 2015)

Organic matter stocks increase with degree of invasion in temperate inland wetlands - J. P. Martina; S. K. Hamilton; M. R. Turetsky; C. J. Phillippo (Plant and Soil, 2014)

siRNA-Mediated Knockdown of P450 Oxidoreductase in Rats: A Tool to Reduce Metabolism by CYPs and Increase Exposure of High Clearance Compounds - Rob S. Burke; Inthirai Somasuntharam; Paul Rearden; Duncan Brown; Sujal V. Deshmukh; Martha A. DiPietro; Jillian DiMuzio; Roy Eisenhandler; Scott E. Fauty; Christopher Gibson; Marian E. Gindy; Kelly A. Hamilton; et al. (Pharmaceutical Research, 2014)

Stratigraphic and depositional framework of the Walloon Subgroup, eastern Surat Basin, Queensland - S. K. Hamilton; J. S. Esterle; R. Sliwa (Australian Journal of Earth Sciences, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Assessing rice and wheat germplasm collections using similarity groups - Th. Hazekamp; T. S. Payne; N. R. Sackville Hamilton (Genetic Resources and Crop Evolution, 2014)

Transcriptional responses in a D rosophila defensive symbiosis - Phineas T. Hamilton; Jong S. Leong; Ben F. Koop; Steve J. Perlman (Molecular Ecology, 2014)
Inherited symbionts are ubiquitous in insects and can have important consequences for the fitness of their hosts. Many inherited symbionts defend their hosts against parasites or other natural enemies; however, the means by which most symbionts confer protection is virtually unknown. We examine the mechanisms of defence in a recently discovered case of symbiont‐mediated protection, where the bacterial symbiont S piroplasma defends the fly D rosophila neotestacea from a virulent nematode parasite, H owardula aoronymphium . Using quantitative PCR of S piroplasma infection intensities and whole transcriptome sequencing, we attempt to distinguish between the following modes of defence: symbiont–parasite competition, host immune priming and the production of toxic factors by S piroplasma . Our findings do not support a model of exploitative competition between H owardula and S piroplasma to mediate defence, nor do we find strong support for host immune priming during S piroplasma infection. Interestingly, we recovered sequence for putative toxins encoded by S piroplasma , including a novel putative ribosome‐inactivating protein, transcripts of which are up‐regulated in response to nematode exposure. Protection via the production of toxins may be a widely used and important mechanism in heritable defensive symbioses in insects.

Topographic and stochastic influences on pāhoehoe lava lobe emplacement - Christopher W. Hamilton; Lori S. Glaze; Mike R. James; Stephen M. Baloga (Bulletin of Volcanology, 2013)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Fine mapping of type 1 diabetes regions Idd9.1 and Idd9.2 reveals genetic complexity - Emma E. Hamilton-Williams; Daniel B. Rainbow; Jocelyn Cheung; Mikkel Christensen; Paul A. Lyons; Laurence B. Peterson; Charles A. Steward; Linda A. Sherman; Linda S. Wicker (Mammalian Genome, 2013)

Holocene paleoecology of a wild rice (Zizania sp.) lake in Northwestern Ontario, Canada - M. Boyd; C. Surette; J. Surette; I. Therriault; S. Hamilton (Journal of Paleolimnology, 2013)

Supramodal and modality-sensitive representations of perceived action categories in the human brain - Richard Ramsey; Emily S. Cross; Antonia F. de C. Hamilton (Experimental Brain Research, 2013)

Influence of Intra- and Interspecific Interactions on Short-term Movement of the Amphipod Corophium volutator in Varying Environmental Conditions - David Drolet; Michael R. S. Coffin; Myriam A. Barbeau; Diana J. Hamilton (Estuaries and Coasts, 2013)

Dynamics of the continent‐wide spread of a Drosophila defensive symbiont - Sarah N. Cockburn; Tamara S. Haselkorn; Phineas T. Hamilton; Elizabeth Landzberg; John Jaenike; Steve J. Perlman (Ecology Letters, 2013)
Facultative symbionts can represent important sources of adaptation for their insect hosts and thus have the potential for rapid spread. Drosophila neotestacea harbours a heritable symbiont, Spiroplasma , that confers protection against parasitic nematodes. We previously found a cline in Spiroplasma prevalence across central Canada, ending abruptly at the Rocky Mountains. Resampling these populations 9 years later revealed that Spiroplasma had increased substantially across the region, resembling a Fisherian wave of advance. Associations between Spiroplasma infection and host mitochondrial DNA indicate that the increase was due to local increase of Spiroplasma ‐infected flies. Finally, we detected Spiroplasma west of the Rocky Mountains for the first time and showed that defence against nematodes occurs in flies with a western genetic background. Because nematode infection is common throughout D. neotestacea 's range, we expect Spiroplasma to spread to the Pacific coast.

A Male-Predominant Cuticular Hydrocarbon, 7-Methyltricosane, is used as a Contact Pheromone in the Western Flower Thrips Frankliniella occidentalis - Oladele A. Olaniran; Akella V. S. Sudhakar; Falko P. Drijfhout; Ian A. N. Dublon; David R. Hall; James G. C. Hamilton; William D. J. Kirk (Journal of Chemical Ecology, 2013)

Case studies of scenario analysis for adaptive management of natural resource and infrastructure systems - Michelle C. Hamilton; Shital A. Thekdi; Elisabeth M. Jenicek; Russell S. Harmon; Michael E. Goodsite; Michael P. Case; Christopher W. Karvetski; James H. Lambert (Environment Systems and Decisions, 2013)

Thermodesulfobacterium geofontis sp. nov., a hyperthermophilic, sulfate-reducing bacterium isolated from Obsidian Pool, Yellowstone National Park - Scott D. Hamilton-Brehm; Robert A. Gibson; Stefan J. Green; Ellen C. Hopmans; Stefan Schouten; Marcel T. J. van der Meer; John P. Shields; Jaap S. S. Damsté; James G. Elkins (Extremophiles, 2013)

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

A common antifungal defense strategy in Cryptocercus woodroaches and termites - M. S. Bulmer; D. Denier; J. Velenovsky; C. Hamilton (Insectes Sociaux, 2012)

Analysis of the transcriptome of differentiating and non-differentiating preadipocytes from rats and humans by next generation sequencing - Fabian Birzele; Sybille Fässler; Heike Neubauer; Tobias Hildebrandt; Bradford S. Hamilton (Molecular and Cellular Biochemistry, 2012)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

A community-based framework for aquatic ecosystem models - Dennis Trolle; David P. Hamilton; Matthew R. Hipsey; Karsten Bolding; Jorn Bruggeman; Wolf M. Mooij; Jan H. Janse; Anders Nielsen; Erik Jeppesen; J. Alex Elliott; Vardit Makler-Pick; Thomas Petzoldt; et al. (Hydrobiologia, 2012)

Fishing top predators indirectly affects condition and reproduction in a reef‐fish community - S. M. Walsh; S. L. Hamilton; B. I. Ruttenberg; M. K. Donovan; S. A. Sandin (Journal of Fish Biology, 2012)
To examine the indirect effects of fishing on energy allocation in non‐target prey species, condition and reproductive potential were measured for five representative species (two‐spot red snapper Lutjanus bohar , arc‐eye hawkfish Paracirrhites arcatus , blackbar devil Plectroglyphidodon dickii , bicolour chromis Chromis margaritifer and whitecheek surgeonfish Acanthurus nigricans ) from three reef‐fish communities with different levels of fishing and predator abundance in the northern Line Islands, central Pacific Ocean. Predator abundance differed by five to seven‐fold among islands, and despite no clear differences in prey abundance, differences in prey condition and reproductive potential among islands were found. Body condition (mean body mass adjusted for length) was consistently lower at sites with higher predator abundance for three of the four prey species. Mean liver mass (adjusted for total body mass), an indicator of energy reserves, was also lower at sites with higher predator abundance for three of the prey species and the predator. Trends in reproductive potential were less clear. Mean gonad mass (adjusted for total body mass) was high where predator abundance was high for only one of the three species in which it was measured. Evidence of consistently low prey body condition and energy reserves in a diverse suite of species at reefs with high predator abundance suggests that fishing may indirectly affect non‐target prey‐fish populations through changes in predation and predation risk.

Susceptibility of rice to sheath blight: an assessment of the diversity of rice germplasm according to genetic groups and morphological traits - L. Willocquet; M. Noel; R. Sackville Hamilton; S. Savary (Euphytica, 2012)

Urban particulate matter activates Akt in human lung cells - Todd L. Watterson; Brett Hamilton; Randy S. Martin; Roger A. Coulombe (Archives of Toxicology, 2012)

The effect of carbohydrate mouth rinse on maximal strength and strength endurance - Vitor S. Painelli; Hamilton Roschel; Bruno Gualano; Serena Del-Favero; Fabiana B. Benatti; Carlos Ugrinowitsch; Valmor Tricoli; Antonio H. Lancha (European Journal of Applied Physiology, 2011)

Biological nitrogen fixation in acidic high‐temperature geothermal springs in Yellowstone National Park, Wyoming - Trinity L. Hamilton; Rachel K. Lange; Eric S. Boyd; John W. Peters (Environmental Microbiology, 2011)
Summary The near ubiquitous distribution of nifH genes in sediments sampled from 14 high‐temperature (48.0–89.0°C) and acidic (pH 1.90–5.02) geothermal springs in Yellowstone National Park suggested a role for the biological reduction of dinitrogen (N 2 ) to ammonia (NH 3 ) (e.g. nitrogen fixation or diazotrophy) in these environments. nifH genes from these environments formed three unique phylotypes that were distantly related to acidiphilic, mesophilic diazotrophs. Acetylene reduction assays and 15 N 2 tracer studies in microcosms containing sediments sampled from acidic and high‐temperature environments where nifH genes were detected confirmed the potential for biological N 2 reduction in these environments. Rates of acetylene reduction by sediment‐associated populations were positively correlated with the concentration of NH 4 + , suggesting a potential relationship between NH 4 + consumption and N 2 fixation activity. Amendment of microcosms with NH 4 + resulted in increased lag times in acetylene reduction assays. Manipulation of incubation temperature and pH in acetylene reduction assays indicated that diazotrophic populations are specifically adapted to local conditions. Incubation of sediments in the presence of a N 2 headspace yielded a highly enriched culture containing a single nifH phylotype. This phylotype was detected in all 14 geothermal spring sediments examined and its abundance ranged from ∼780 to ∼6800 copies (g dry weight sediment) −1 , suggesting that this organism may contribute N to the ecosystems. Collectively, these results for the first time demonstrate thermoacidiphilic N 2 fixation in the natural environment and extend the upper temperature for biological N 2 fixation in terrestrial systems.

EGFL6 is increasingly expressed in human obesity and promotes proliferation of adipose tissue-derived stromal vascular cells - Rupert Oberauer; Wolfgang Rist; Martin C. Lenter; Bradford S. Hamilton; Heike Neubauer (Molecular and Cellular Biochemistry, 2010)

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

IgE antibody-specific activity in human allergic disease - Robert G. Hamilton; Donald W. MacGlashan; Sarbjit S. Saini (Immunologic Research, 2010)

Contorted and ordinary body postures in the human brain - Emily S. Cross; Emilie C. Mackie; George Wolford; Antonia F. de C. Hamilton (Experimental Brain Research, 2010)

Conserved regulatory motifs at phenylethanolamine N-methyltransferase (PNMT) are disrupted by common functional genetic variation: an integrated computational/experimental approach - Juan L. Rodríguez-Flores; Kuixing Zhang; Sun Woo Kang; Gen Wen; Sajalendu Ghosh; Ryan S. Friese; Sushil K. Mahata; Shankar Subramaniam; Bruce A. Hamilton; Daniel T. O’Connor (Mammalian Genome, 2010)

Evidence of a North Atlantic right whale calf ( Eubalaena glacialis ) born in northeastern U.S. waters - Melissa R. Patrician; Ingrid S. Biedron; H. Carter Esch; Frederick W. Wenzel; Lindsay A. Cooper; Philip K. Hamilton; Allison H. Glass; Mark F. Baumgartner (Marine Mammal Science, 2009)

Genetic variation in strains of zebrafish (Danio rerio) and the implications for ecotoxicology studies - T. S. Coe; P. B. Hamilton; A. M. Griffiths; D. J. Hodgson; M. A. Wahab; C. R. Tyler (Ecotoxicology, 2009)

Assimilatory uptake rather than nitrification and denitrification determines nitrogen removal patterns in streams of varying land use - C. P. Arango; J. L. Tank; L. T. Johnson; S. K. Hamilton (Limnology and Oceanography, 2008)
Agricultural and urban land use increase nitrogen (N) concentrations in streams, which can saturate biotic demand by plants, algae, and bacteria via assimilative uptake, and by nitrification and denitrification. We studied six streams per year in each of three land‐use categories (agricultural, urban, and forested) for 3 yr ( n = 18 streams), and we compared whole‐stream N uptake and microbial N transformation rates during spring, summer, and autumn. We measured whole‐stream removal of added ammonium (NH 4 + ) and nitrate (NO 3 − ) in the field and quantified sediment nitrification and denitrification rates in laboratory assays. Relative demand for NNH 4 + (as uptake velocity, Vf) was highest in spring and in streams with open canopies, implying a link with aquatic autotrophy. In agricultural and urban streams, whole‐stream removal (as areal uptake, U) of NH 4 + and NO 3 − , nitrification, and denitrification rates approached saturation at higher inorganic N concentrations. Nitrification and denitrification rates measured in redox‐optimized laboratory assays were roughly equivalent, suggesting that in situ redox conditions will determine whether stream sediments are a net source or sink of NO 3 − . Though nitrification and denitrification rates were measured under ideal redox conditions, they were always more than an order of magnitude lower than whole‐stream NO{3 uptake, demonstrating their limited influence on wholestream NO 3 − dynamics. Assimilatory processes, which temporarily store N removed from the water column, dominated whole‐stream N demand and controlled downstream N flux. The ultimate fate of assimilated N remains unknown; in‐channel storage cannot account for it, and thus a key question is what fraction may eventually be stored in downstream depositional zones or denitrified upon remineralization.

Effective population size dynamics reveal impacts of historic climatic events and recent anthropogenic pressure in African elephants - J. B. A. OKELLO; G. WITTEMYER; H. B. RASMUSSEN; P. ARCTANDER; S. NYAKAANA; I. DOUGLAS‐HAMILTON; H. R. SIEGISMUND (Molecular Ecology, 2008)
Two hundred years of elephant hunting for ivory, peaking in 1970–1980s, caused local extirpations and massive population declines across Africa. The resulting genetic impacts on surviving populations have not been studied, despite the importance of understanding the evolutionary repercussions of such human‐mediated events on this keystone species. Using Bayesian coalescent‐based genetic methods to evaluate time‐specific changes in effective population size, we analysed genetic variation in 20 highly polymorphic microsatellite loci from 400 elephants inhabiting the greater Samburu‐Laikipia region of northern Kenya. This area experienced a decline of between 80% and 90% in the last few decades when ivory harvesting was rampant. The most significant change in effective population size, however, occurred approximately 2500 years ago during a mid–Holocene period of climatic drying in tropical Africa. Contrary to expectations, detailed analyses of four contemporary age‐based cohorts showed that the peak poaching epidemic in the 1970s caused detectable temporary genetic impacts, with genetic diversity rebounding as juveniles surviving the poaching era became reproductively mature. This study demonstrates the importance of climatic history in shaping the distribution and genetic history of a keystone species and highlights the utility of coalescent‐based demographic approaches in unravelling ancestral demographic events despite a lack of ancient samples. Unique insights into the genetic signature of mid‐Holocene climatic change in Africa and effects of recent poaching pressure on elephants are discussed.

The production and emission of nitrous oxide from headwater streams in the Midwestern United States - J. J. BEAULIEU; C. P. ARANGO; S. K. HAMILTON; J. L. TANK (Global Change Biology, 2008)
The emission of nitrous oxide (N 2 O) from streams draining agricultural landscapes is estimated by the Intergovernmental Panel on Climate Change (IPCC) to constitute a globally significant source of this gas to the atmosphere, although there is considerable uncertainty in the magnitude of this source. We measured N 2 O emission rates and potential controlling variables in 12 headwater streams draining a predominantly agricultural basin on glacial terrain in southwestern Michigan. The study sites were nearly always supersaturated with N 2 O and emission rates ranged from −8.9 to 266.8 μg N 2 O‐N m −2 h −1 with an overall mean of 35.2 μg N 2 O‐N m −2 h −1 . Stream water NO 3 − concentrations best‐predicted N 2 O emission rates. Although streams and agricultural soils in the basin had similar areal emission rates, emissions from streams were equivalent to 6% of the anthropogenic emissions from soils because of the vastly greater surface area of soils. We found that the default value of the N 2 O emission factor for streams and groundwater as defined by the IPCC (EF5‐g) was similar to the value observed in this study lending support to the recent downward revision to EF5‐g. However, the EF5‐g spanned four orders of magnitude across our study sites suggesting that the IPCC's methodology of applying one emission factor to all streams may be inappropriate.

Sexual development and reproductive demography of the green humphead parrotfish (Bolbometopon muricatum) in the Solomon Islands - R. J. Hamilton; S. Adams; J. H. Choat (Coral Reefs, 2008)

Patterns of male reproductive success in a highly promiscuous whale species: the endangered North Atlantic right whale - T. R. FRASIER; P. K. HAMILTON; M. W. BROWN; L. A. CONGER; A. R. KNOWLTON; M. K. MARX; C. K. SLAY; S. D. KRAUS; B. N. WHITE (Molecular Ecology, 2007)
Parentage analyses of baleen whales are rare, and although mating systems have been hypothesized for some species, little data on realized male reproductive success are available and the patterns of male reproductive success have remained elusive for most species. Here we combine over 20 years of photo‐identification data with high‐resolution genetic data for the majority of individual North Atlantic right whales to assess paternity in this endangered species. There was significant skew in male reproductive success compared to what would be expected if mating was random ( P 0.001). The difference was due to an excess of males assigned zero paternities, a deficiency of males assigned one paternity, and an excess of males assigned as fathers for multiple calves. The variance in male reproductive success was high relative to other aquatically mating marine mammals, but was low relative to mammals where the mating system is based on resource‐ and/or mate‐defence polygyny. These results are consistent with previous data suggesting that the right whale mating system represents one of the most intense examples of sperm competition in mammals, but that sperm competition on its own does not allow for the same degree of polygyny as systems where males can control access to resources and/or mates. The age distribution of assigned fathers was significantly biased towards older males ( P 0.05), with males not obtaining their first paternity until ~15 years of age, which is almost twice the average age of first fertilization in females (8 years), suggesting that mate competition is preventing younger males from reproducing. The uneven distribution of paternities results in a lower effective population size in this species that already has one of the lowest reported levels of genetic diversity, which may further inhibit reproductive success through mate incompatibility of genetically similar individuals.

The impact of climate change on tourism in Germany, the UK and Ireland: a simulation study - Jacqueline M. Hamilton; Richard S. J. Tol (Regional Environmental Change, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A standardized nomenclature for the mouse and rat prolactin superfamilies - Michael J. Soares; S. M. Khorshed Alam; Mary Lynn Duckworth; Nelson D. Horseman; Toshihiro Konno; Daniel I. H. Linzer; Lois J. Maltais; Marit Nilsen-Hamilton; Kunio Shiota; Jennifer R. Smith; Michael Wallis (Mammalian Genome, 2007)

Hierarchical components of genetic variation at a species boundary: population structure in two sympatric varieties of Lupinus microcarpus (Leguminosae) - CHRISTOPHER S. DRUMMOND; MATTHEW B. HAMILTON (Molecular Ecology, 2007)
Lupinus microcarpus is a self‐compatible annual plant that forms a species complex of morphologically variable but indeterminate varieties. In order to examine the hypothesis that varieties of L. microcarpus comprise genetically differentiated and reproductively isolated species, populations of L. microcarpus var. horizontalis and var. densiflorus were sampled from an area of sympatry in central California and genotyped using six microsatellite loci. Bayesian clustering divided the total sample into two groups corresponding to the named varieties with extremely low levels of inferred coancestry. Similarly, maximum likelihood and distance methods for genetic assignment placed individuals in two nonoverlapping groups. Evidence for isolation by distance (IBD) within each variety was found at shorter distance classes, but varieties remained differentiated in sympatry. Furthermore, coalescent estimates of divergence time indicate separation within the past 950–5050 generations, with minimal gene flow after divergence. A four‐level hierarchical analysis of molecular variance ( amova ) found significant levels of genetic differentiation among varieties (θ P = 0.292), populations within varieties (θ S = 0.449), subpopulations within populations (θ SS = 0.623), and individuals within subpopulations ( f = 0.421); but the greatest degree of differentiation was at the subpopulation level. Although it is sometimes assumed that the magnitude of genetic differences (e.g. F ST ) should be greater between species than among populations or subpopulations of the same species, shared ancestral polymorphism may lead to relatively low levels of differentiation at the species level, even as the stochastic effects of genetic drift generate higher levels of differentiation at lower hierarchical levels. These results suggest that L. microcarpus var. horizontalis and var. densiflorus are recently diverged yet reproductively isolated species, with high levels of inbreeding resulting from the combined effects of limited gene flow, demographic bottlenecks, and partial selfing in finite, geographically structured populations.

Predicting tourism flows under climate change - Andrea Bigano; Jacqueline M. Hamilton; David J. Maddison; Richard S. J. Tol (Climatic Change, 2006)

Analysis of the incidence of infectious pancreatic necrosis mortality in pedigreed Atlantic salmon, Salmo salar L., populations - D R Guy; S C Bishop; S Brotherstone; A Hamilton; R J Roberts; B J McAndrew; J A Woolliams (Journal of Fish Diseases, 2006)
A total of 77 124 Atlantic salmon post‐smolts, representing 197 full‐sib families produced by 149 males and 197 females, experienced a field challenge from infectious pancreatic necrosis virus (IPNV), following transfer to three separate seawater sites. The first IPN mortality was observed 45 days after transfer, and the duration of the epidemic varied between 37 and 92 days among sites. Mortalities were traced to their parental families by PIT (Passive Integrated Transpondes) tag records and DNA genotyping. Full‐sib family mean incidence of mortality was calculated for each family on each site. Heritabilities were estimated based on the heterogeneity of chi‐square using incidence within half‐sib families and the variance in incidence among full‐sib families, both on the observed and underlying liability scale. The observed correlation among families across sites was used to estimate genetic correlations. The overall mortality rate was 10.8%, with only small differences between sites, ranging from 10.3% to 11.9%. Heritabilities on the liability scale were found to be moderate to strong, and ranged between 0.24 and 0.81, with a pooled estimate of 0.43, greater than is typically associated with disease traits. Genetic correlations among sites were all substantial, between 0.71 and 0.78, and indicated that a substantial component of the genetic variation displayed within sites was common to all. The results show that field challenges can yield very good genetic information on family differences in resistance, especially when replicated over sites, which may then be developed for use in selection for breeding strains of Atlantic salmon with greater resistance to IPN.

Expressed Sequence Tags from loblolly pine embryos reveal similarities with angiosperm embryogenesis - John Cairney; Li Zheng; Allison Cowels; Joseph Hsiao; Victoria Zismann; Jia Liu; Shu Ouyang; Francoise Thibaud-Nissen; John Hamilton; Kevin Childs; Gerald S. Pullman; Yiting Zhang; et al. (Plant Molecular Biology, 2006)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Geographical Clustering of Pancreatic Cancers in the Northeast Nile Delta Region of Egypt - A. S. Soliman; X. Wang; J.-D. Stanley; N. El-Ghawalby; M. L. Bondy; F. Ezzat; A. Soultan; M. Abdel-Wahab; O. Fathy; G. Ebidi; N. Abdel-Karim; K.-Anh. Do; et al. (Archives of Environmental Contamination and Toxicology, 2006)

The Impact of Climate on Holiday Destination Choice - Andrea Bigano; Jacqueline M. Hamilton; Richard S. J. Tol (Climatic Change, 2006)

The Complete Nucleotide Sequence and Genomic Organization of Citrus Leprosis Associated Virus, Cytoplasmatic type (CiLV-C) - Renata C. Pascon; João Paulo Kitajima; Michèle C. Breton; Laura Assumpção; Christian Greggio; Almir S. Zanca; Vagner Katsumi Okura; Marcos C. Alegria; Maria E. Camargo; Giovana G.C. Silva; Jussara C. Cardozo; Marcelo A. Vallim; et al. (Virus Genes, 2006)

Hinge peptide combinatorial libraries for inhilbitors of botulinum neurotoxins and saxitoxin: Deconvolution strategy - Graham J. Moore; Diana M. Moore; Samir S. Roy; Lawrence J. Hayden; Murray G. Hamilton; Nora W. C. Chan; William E. Lee (Molecular Diversity, 2006)

Does Breeding Site Fidelity Drive Phenotypic and Genetic Sub-Structuring of a Population of Arctic Charr? - Colin E. Adams; Deborah J. Hamilton; Ian Mccarthy; Alastair J. Wilson; Alan Grant; Gavin Alexander; Susan Waldron; Sigurdur S. Snorasson; Moira M. Ferguson; Skuli Skúlason (Evolutionary Ecology, 2006)

Selenium in the Blackfoot, Salt, and Bear River Watersheds - S. J. Hamilton; K. J. Buhl (Environmental Monitoring and Assessment, 2005)

Letters - Scott Kiewit; Richard G. Reid; Lawrence S. Hamilton (Journal of Forestry, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Genetic identification of two sibling species of Lutzomyia longipalpis (Diptera: Psychodidae) that produce distinct male sex pheromones in Sobral, Ceará State, Brazil - R. D. C. Maingon; R. D. Ward; J. G. C. Hamilton; H. A. Noyes; N. Souza; S. J. Kemp; P. C. Watts (Molecular Ecology, 2003)
Lutzomyia longipalpis , the main sandfly vector for New World visceral leishmaniasis is a complex of an as yet undefined number of sibling species. At present, there is no consensus on the status (single species vs. species complex) of Brazilian populations. We applied five microsatellite loci to test the hypothesis that L. longipalpis occurs as two sympatric cryptic species in Sobral, Ceará State, Brazil as predicted by male sex pheromone chemotypes described previously for field specimens from this site [ S‐ 9‐methyl‐germacrene‐B ( 9MGB) and a cembrene compound]. Abdominal spot morphology corresponds with pheromone type at this locality (9MGB in ‘1 spot’ males and cembrene in ‘2 spot’ males). Genotype data from 190 wild‐caught L. longipalpis specimens collected in October 1999 and April 2001 were used to estimate genetic differentiation between the two sex pheromone populations and sampling dates. No significant ( P > 0.05) genetic differences were found between the 1999 and 2001 9MGB samples (θ = 0.018; R ST = −0 . 005), and genetic differentiation was low between the cembrene collections (θ = 0.037, P R ST = −0.043, P > 0.05). By contrast, highly divergent allelic frequencies (largely at two microsatellite loci) corresponded to significant ( P > 0.05) genetic differentiation (θ = 0.221; R ST = 0.215) for all comparisons between samples with different pheromones. When pheromone samples were pooled across sample date, genetic differentiation was high (θ = 0.229; P N e m = 0.84). The allele frequency distribution at each of the five microsatellite loci was similar for males and females from the two collection years. Two of these loci showed highly divergent allele frequencies in the two sex pheromone populations. This was reflected in the highly significant genetic differentiation obtained from the male genotypes, between populations producing different pheromones (θ = 0.229–0.268; P P L. longipalpis .

Cytogenetic Effect of Organoarsenicals on Cultured Mammalian Cells - T. S. Kochhar; B. Hamilton; M. Autry (Bulletin of Environmental Contamination and Toxicology, 2003)

Evolutionary Ecology: Integrating Theory, Technology, and Ecology - C. R. Hurt; S. Meredith; P. Hamilton (Conservation Biology, 2003)

Molecular genecology of temperature response in Lolium perenne : 1. preliminary analysis to reduce false positives - N. R. Sackville Hamilton; L. Skøt; K. H. Chorlton; I. D. Thomas; S. Mizen (Molecular Ecology, 2002)
Molecular genecology is the study of geographical clines in frequencies of molecular markers and their relationship to ecological clines in environmental conditions. This study outlines the principles underlying the selection of populations, focusing on avoiding ‘false positives’— noncausal correlations between allele frequency and the environment. The principles are illustrated by identifying a set of populations of Lolium perenne for the study of temperature responses. The selected set of populations encompasses a 20 °C range in mean January temperature. Their freezing tolerance shows a linear trend with winter temperature, LT 50 decreasing by 0.25 °C for each 1 °C reduction in mean January temperature.

Molecular genecology of temperature response in Lolium perenne : 2. association of AFLP markers with ecogeography - L. Skøt; N. R. Sackville Hamilton; S. Mizen; K. H. Chorlton; I. D. Thomas (Molecular Ecology, 2002)
Improved winter hardiness is an important breeding objective in the forage grass Lolium perenne . This is a complex trait with several components, including the ability to survive and grow at low temperature, to acclimate to cold, tolerate wind, snow cover and ice encasement. Marker‐assisted selection has the potential to increase the efficiency of breeding for improved cold tolerance. Here we describe a genecological approach to identifying molecular markers that are associated with adaptation to low winter temperatures. AFLP was used to assess the genetic diversity in 29 wild populations of ryegrass ( Lolium perenne ) representing a pan‐European temperature cline in terms of their geographical origin. A further 18 populations from a temperature cline in Bulgaria were also analysed. In addition, two varieties and five populations representing parents of mapping families currently in use at IGER were included in the analysis. Principal coordinate (PCoA) and cluster analyses of the molecular marker data showed that the Bulgarian altitude cline populations could be distinguished clearly from the other populations. Two regression analyses were carried out; one to identify AFLP markers that correlated in frequency with low mean January temperature of the geographical origin of the population, and another to identify AFLP markers correlating in frequency with the cold tolerance phenotype of the populations, as determined by LT 50 values in freezing tests. In the first analysis six AFLP markers showed significant type II trends with mean January temperature, and in the second analysis 28 bands had a significant univariate relationship with the LT 50 value of the accessions. In steps 2 and 3 of the stepwise analysis a further 4 and 5 bands, respectively, improved the fit significantly. The results of the two types of regression analysis are discussed in relation to ecogeography and cold tolerance phenotype of the populations.

The tetratricopeptide repeat domains of human, tobacco, and nematode PEX5 proteins are functionally interchangeable with the analogous native domain for peroxisomal import of PTS1-terminated proteins in yeast - A. Gurvitz; L. Wabnegger; S. Langer; B. Hamilton; H. Ruis; A. Hartig (Molecular Genetics and Genomics, 2001)

Mean Annual Temperature and Total Annual Precipitation Trends at Canadian Biosphere Reserves - James P. Hamilton; Graham S. Whitelaw; Adam Fenech (Environmental Monitoring and Assessment, 2001)

Trace Elements in Seep Waters Along Whitewood Creek, South Dakota, and Their Toxicity to Fathead Minnows - S. J. Hamilton, K. J. Buhl (Bulletin of Environmental Contamination and Toxicology, 2000)

Characterisation of marine and lacustrine sediments in a drowned thermokarst embayment, Richards Island, Beaufort Sea, Canada - S. Solomon; P. J. Mudie; R. Cranston; T. Hamilton; S. A. Thibaudeau; E. S. Collins (International Journal of Earth Sciences, 2000)

Trace Elements in Seep Waters Along Whitewood Creek, South Dakota, and Their Toxicity to Fathead Minnows - S. J. Hamilton; K. J. Buhl (Bulletin of Environmental Contamination and Toxicology, 2000)

World‐wide genetic differentiation of Eubalaena : questioning the number of right whale species - H. C. Rosenbaum; R. L. Brownell; M. W. Brown; C. Schaeff; V. Portway; B. N. White; S. Malik; L. A. Pastene; N. J. Patenaude; C. S. Baker; M. Goto; P. B. Best; et al. (Molecular Ecology, 2000)
Few studies have examined systematic relationships of right whales ( Eubalaena spp.) since the original species descriptions, even though they are one of the most endangered large whales. Little morphological evidence exists to support the current species designations for Eubalaena glacialis in the northern hemisphere and E. australis in the southern hemisphere. Differences in migratory behaviour or antitropical distribution between right whales in each hemisphere are considered a barrier to gene flow and maintain the current species distinctions and geographical populations. However, these distinctions between populations have remained controversial and no study has included an analysis of all right whales from the three major ocean basins. To address issues of genetic differentiation and relationships among right whales, we have compiled a database of mitochondrial DNA control region sequences from right whales representing populations in all three ocean basins that consist of: western North Atlantic E. glacialis , multiple geographically distributed populations of E. australis and the first molecular analysis of historical and recent samples of E. glacialis from the western and eastern North Pacific Ocean. Diagnostic characters, as well as phylogenetic and phylogeographic analyses, support the possibility that three distinct maternal lineages exist in right whales, with North Pacific E. glacialis being more closely related to E. australis than to North Atlantic E. glacialis . Our genetic results provide unequivocal character support for the two usually recognized species and a third distinct genetic lineage in the North Pacific under the Phylogenetic Species Concept, as well as levels of genetic diversity among right whales world‐wide.

Book Review: FEDERALISM AND ENVIRONMENTAL POLICY: TRUST AND THE POLITICS OF IMPLEMENTATION. By Denise Scheberle. Georgetown University Press, 1997, 224 pp., $20.95. ISBN 0878406565 - Michael S. Hamilton (Environmental Management, 2000)

Pollen‐based biome reconstruction for southern Europe and Africa 18,000 yr bp - H. Elenga; O. Peyron; R. Bonnefille; D. Jolly; R. Cheddadi; J. Guiot; V. Andrieu; S. Bottema; G. Buchet; J.‐L. De Beaulieu; A. C. Hamilton; J. Maley; et al. (Journal of Biogeography, 2000)
Pollen data from 18,000 14 C yr bp were compiled in order to reconstruct biome distributions at the last glacial maximum in southern Europe and Africa. Biome reconstructions were made using the objective biomization method applied to pollen counts using a complete list of dryland taxa wherever possible. Consistent and major differences from present‐day biomes are shown. Forest and xerophytic woods/scrub were replaced by steppe, both in the Mediterranean region and in southern Africa, except in south‐western Cape Province where fynbos (xerophytic scrub) persisted. Sites in the tropical highlands, characterized today by evergreen forest, were dominated by steppe and/or xerophytic vegetation (cf. today’s Ericaceous belt and Afroalpine grassland) at the last glacial maximum. Available data from the tropical lowlands are sparse but suggest that the modern tropical rain forest was largely replaced by tropical seasonal forest while the modern seasonal or dry forests were encroached on by savanna or steppe. Montane forest elements descended to lower elevations than today.

Testing Models of Chemical Speciation in Freshwaters - S. Bryan; E. Tipping; J. Hamilton-Taylor (Environmental Geochemistry and Health, 1999)

RELATIVE ABUNDANCE OF LARGE WHALES AROUND SOUTH GEORGIA (1979–1998) 1 - M. J. Moore; S. D. Berrow; B. A. Jensen; P. Carr; R. Sears; V. J. Rowntree; R. Payne; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract To assess large‐whale stocks following the cessation of land‐based South Georgia whaling in 1965, we report three independent sighting databases: a cruise in 1997, observations from Bird Island (NW of South Georgia) between 1979 and 1998, and mariner sightings between 1992 and 1997. All species were rare, with sightings of southern right whales being the most common event. Two right whales photographed off South Georgia matched animals known from Peninsula Valdés, Argentina, a population known to be growing at 7% per annum . In contrast, blue and fin whales appeared to be less abundant. A single blue whale mother‐calf pair was observed off the Shag Rocks in February 1997. Extirpation of animals from this particular feeding ground is the most likely reason for ongoing low numbers of all species. Other factors may include competition for krill by traditional predators such as penguins and seals and more recently by humans, an unusually high rate of natural mortality, habitat change such as alteration in sea ice coverage, and/or the impact of ongoing whaling. The history of this critical area of large‐whale habitat and this report demonstrate the need for improved, consistent longterm monitoring of population trends for these depleted stocks.

DNA Sequence Evidence for Placement of the Ground Cuscus, Phalanger gymnotis, in the Tribe Phalangerini (Marsupialia: Phalangeridae) - Aaron T. Hamilton; Mark S. Springer (Journal of Mammalian Evolution, 1999)

Microsatellite loci reveal highly significant genetic differentiation among Atlantic salmon ( Salmo salar L.) stocks from the east coast of Canada - S. K. J. McConnell; D. E. Ruzzante; P. T. O'Reilly; L. Hamilton; J. M. Wright (Molecular Ecology, 1997)
Allele frequency data from eight microsatellite loci provide evidence of highly significant genetic differentiation among stocks of Atlantic salmon Salmo salar L. from the Bay of Fundy, eastern and north‐western Nova Scotia and Newfoundland. Estimates of genetic structure ( R ST and θ) were significant both among all samples taken from the different geographical locations and among samples from geographical regions for which more than one stock was sampled. Samples from the Bay of Fundy taken from stocks which are phenotypically and behaviourally diverse showed particularly high levels of genetic structure. Rogers', allele sharing and (δμ) 2 distances also revealed significant differences among stock samples and were significantly correlated [Rogers' and (δμ) 2 ] with sea distance between rivers. Results suggest that stocks of Atlantic salmon in eastern Canada are highly diverse genetically and that this should be an important consideration in any management programme for stocks in the area.

Toxicity of inorganic contaminants, individually and in environmental mixtures, to three endangered fishes (Colorado squawfish, bonytail, and razorback sucker) - K. J. Buhl; S. J. Hamilton (Archives of Environmental Contamination and Toxicology, 1996)

Toxicity of Inorganic Contaminants, Individually and in Environmental Mixtures, to Three Endangered Fishes (Colorado Squawfish, Bonytail, and Razorback Sucker) - K. J. Buhl; S. J. Hamilton (Archives of Environmental Contamination and Toxicology, 1996)

High level production of potyvirus-like particles in insect cells infected with recombinant baculovirus - S. J. Edwards; M. B. Hayden; R. C. Hamilton; J. A. Haynes; I. T. Nisbet; M. N. Jagadish (Archives of Virology, 1994)

Skeletal deformities in smallmouth bass,Micropterus dolomieui, from southern Appalachian reservoirs - M. J. Van Den Avyle; S. J. Garvick; V. S. Blazer; S. J. Hamilton; W. G. Brumbaugh (Archives of Environmental Contamination and Toxicology, 1989)

Kinetics of the respiratory syncytial virus growth cycle in Hela cells - S. Levine; R. Hamilton (Archives of Virology, 1969)